Prospects for constitutionalism in post-communist countries - Gönenç, Levent (Martinus Nijhoff, 2002)
The main questions dealt with throughout this study can be formulated as follows: Will liberal democratic constitutionalism take root in post-communist countries? And will new constitutions in Eastern Europe and the former USSR perish or survive?
Keywords: Constitutional law -- Europe, Eastern.; Post-communism -- Former Soviet republics.; Democracy.; Droit constitutionnel -- Europe de l'Est.; Postcommunisme -- Ex-URSS.; LAW -- Constitutional.; LAW -- Public.; Constitutional law; Democracy; Post-communism; Eastern Europe; Soviet Union -- Former Soviet republics; Demokratisierung; Verfassung; Politische Kultur; Osteuropa; Constitutionalisme.; GUS.